Self-medication practices among university students from Karachi, Pakistan - Limaye, Dnyanesh; Saeed, Farah; Ahmad, Mansoor; Pitani, Ravi Shankar; Fortwengel, Gerhard (International Journal Of Community Medicine And Public Health, 2017)
Background: Self-medication, practiced globally is an important public health problem. Research studies have indicated inappropriate self‐medication results in adverse drug reactions, disease masking, antibiotic resistance and wastage of healthcare resources. The objectives of the study were to explore overall self-medication and antibiotic self-medication prevalence among students of university students in Karachi, Pakistan along with probable reasons, indications, and sources of advice for self-medication. Methods: A descriptive, cross-sectional, questionnaire-based study was carried out among students from university of Karachi, Pakistan during the time period of September to November 2016. Pretested questionnaire was distributed to 320 students, collected data was analyzed using IBM SPSS version 24. Results: From 320 students, 311 (83 male and 228 female) students participated in the study giving a response rate of 97%. Prevalence of self-medication was 66%. Belonging to higher monthly family income group was associated with likelihood of self-medication. Antibiotic self-medication prevalence was 39%. Lack of time (39%), and old prescription (35%) were the main reasons for self-medication. Pharmacy shop (75%) was the main source for self-medication. In case of antibiotics, 44% students changed the dosage of antibiotic and 50% students stopped antibiotics after the disappearance of the symptoms. Conclusions: Antibiotic self-medication (39%) and self-medication with other drugs among university students of Karachi is a worrisome problem. Our findings highlight the need for planning interventions to promote the judicious use of general medicines as well as that of antibiotics.